2014
DOI: 10.12776/ams.v20i1.273
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Aluminium Alloys 2024 –T 3 Form in Terms of Tribocorrosion Characteristics

Abstract: Results of" ball on disc" principle tests to examine the friction coefficient and wear rate of Aluminium Alloys 2024-T3 are presented. Tribocorrosion experiments were performed using a pin on disc tribometer under controlled electrochemical conditions in NaCl solution. This paper reviews the available knowledge relating to the tribocorrosion. Tribocorrosion can be defined as a degradation phenomenon of material surfaces (wear, cracking, corrosion, etc.) subjected to the combined action of mechanical loading (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These failure modes are surface phenomena. They emanate at the surface and can swiftly lead to stress concentration, fracture, increased friction, and other problems caused by the formation of wear debris and corrosion products occurring on rubbing or impacting surfaces [1,2]. Hence there can be corrosion induced wear or wear aggravated corrosion [3] broadly categorized under the tribocorrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These failure modes are surface phenomena. They emanate at the surface and can swiftly lead to stress concentration, fracture, increased friction, and other problems caused by the formation of wear debris and corrosion products occurring on rubbing or impacting surfaces [1,2]. Hence there can be corrosion induced wear or wear aggravated corrosion [3] broadly categorized under the tribocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it to be alkaline and has strong potential to attack aluminium alloy components in the brake system. Studies have been widely reported on the subjects of wear, corrosion and tribocorrosion of different Al alloys [2][3][8][9][10][11]. Aluminium alloy wears have been accessed using tribometers, while their corrosions have been studied in diverse active and aggressive media (acid, base and alkali).…”
Section: Introductionmentioning
confidence: 99%
“…A new experimental device a linear microtribometer is being used for evaluation of tribological properties at the Department of construction and engine parts. The testing is based on the method Ball-on-Plate, which is a standard method of tribological material properties testing [2][3][4]. The main part of a microtribometer is a tribological knot which consists of a ball (fixed on the end of a roller) and a flat sample in a shape of a plate.…”
Section: Methodsmentioning
confidence: 99%
“…The matrix consists of two phases -bainitic ferrite and stabilized austenite. The combination of these two phases in the structure of the matrix enables to reach good mechanical properties of this material [1,2]. HTDI is made of the cast iron with globular graphite by means of standard heat treatment (quenching and tempering).…”
Section: Introductionmentioning
confidence: 99%
“…Such samples with natural passivation ability are stable in corrosion media. In other words, the existence or rebuilding rate of the passivation layer after its damage determine the corrosion resistant of the metallic surface during tribocorrosion processes [1].…”
Section: Introductionmentioning
confidence: 99%